Subjective Collective Will In the Management of Shared Agricultural Land and Its Consequences - V. A. Mayboroda (Теоретическая и прикладная юриспруденция)
A new stage in the development of relations in the management of agricultural land plots has replaced the initial privatization of agricultural land. Its difference is the change in the composition of the participants in the share ownership and the presence of economically strong economic counterparties-tenants of land. The composition of new owners is socially heterogeneous and, as a result, it does not have a legal instrument allowing to form the collective will of the general meeting according to the goals of property management, since the heterogeneity of the composition prevents the emergence of the possibility of unity of management goals. The expression of subjective collective will must have a legal instrument to prevent the possibility of its usurpation by an economically strong subject. It seems that such an instrument should be the differentiation of the types of disputes related to the formation of collective will on the management of common ownership and the procedural peculiarities of their resolution.